Advances in algal biomass pretreatment and its valorisation into biochemical and bioenergy by the microbial processes - Bhatia, Shashi Kant; Ahuja, Vishal; Chandel, Neha; Gurav, Ranjit; Bhatia, Ravi Kant; Govarthanan, Muthusamy; Tyagi, Vinay Kumar; Kumar, Vinod; Pugazendhi, Arivalagan; Banu, J. Rajesh; Yang, Yung-Hun (Elsevier, 2022)
Urbanization and pollution are the major issues of the current time own to the exhaustive consumption of fossil fuels which have a detrimental effect on the nation's economies and air quality due to greenhouse gas (GHG) emissions and shortage of energy reserves. Algae, an autotrophic organism provides a green substitute for energy as well as commercial products. Algal extracts become an efficient source for bioactive compounds having anti-microbial, anti-oxidative, anti-inflammatory, and anti-cancerous potential. Besides the conventional approach, residual biomass from any algal-based process might act as a renewable substrate for fermentation. Likewise, lignocellulosic biomass, algal biomass can also be processed for sugar recovery by different pre-treatment strategies like acid and alkali hydrolysis, microwave, ionic liquid, and ammonia fiber explosion, etc. Residual algal biomass hydrolysate can be used as a feedstock to produce bioenergy (biohydrogen, biogas, methane) and biochemicals (organic acids, polyhydroxyalkanoates) via microbial fermentation.
Keywords: Algal biomass; Fermentation